Positive Youth Development Attributes and Parenting as Protective Factors Against Adolescent Social Networking Addiction in Hong Kong - Yu, Lu; Shek, Daniel Tan Lei (Frontiers in Pediatrics, 2021)
This study examined the predictive effects of 15 positive youth development (PYD) attributes and parenting behavior on adolescent social networking addiction (SNA) in a representative sample of Hong Kong students. In total, 1,896 Hong Kong Secondary 1 students from 20 randomly selected schools (age = 13.19±0.52 years) completed the Bergen Social Media Addiction Scale (BSMAS), the Chinese Positive Youth Development Scale, and the Chinese Parenting Behavior Scale. Of the participants, 11.4% could be classified as being addicted to Social Networking Sites (SNSs). Regression analyses showed that students’ emotional competence (β = -.09; p < .01), behavioral competence (β = -.12; p < .001), beliefs in the future (β = -.10; p < .01), and spirituality (β = -.08; p < .01) were negatively associated with SNA, while social competence (β = .07; p < .05) and positive identity (β = .13; p < .001) were positively related to SNA. Paternal and maternal responsiveness showed indirect effects on students’ SNA through the full mediation of PYD attributes. Specific PYD attributes and positive parenting behavior may serve as important protective factors against the development of SNA among Hong Kong adolescents.